CGIAR Food Systems Accelerator: bootcamp report – Kenya - Nyauncho, E.; Mabele, Thato; Nguvi, C.; Kirimi, P.; Njiru-Mugo, A.; Nkosi, Mahlatse; Petersen, N.; Mugo, P.; Sewe, L. (International Water Management Institute (IWMI), 2024)
The CGIAR Food Systems Accelerator (CFSA) Bootcamp, held in Nairobi, Kenya, from October 2–4, 2024, convened 40 agribusiness SMEs from Nairobi and surrounding counties, investors, and technical experts to equip businesses with tools for scaling climate-smart agriculture solutions. Organized under the Ukama Ustawi Initiative, the bootcamp aimed to bridge the gap between innovation, investment readiness, and sustainable food systems through a structured, three-day program. The bootcamp underscored the critical role of targeted support for agribusiness SMEs in East and Southern Africa, which often lack access to capital, expertise, and markets. By fostering collaborations between businesses, technical experts, and investors, the program positioned SMEs to drive climate resilience, food security, and economic growth. Unlike traditional accelerator programs, CFSA’s science-driven, climate-resilient, and gender-inclusive approach uniquely addresses the region’s challenges, ensuring agribusinesses are not just investment-ready but also equipped for long-term sustainability. Given the high demand for capacity-building initiatives of this nature, expanding the bootcamp model to additional African regions could provide more SMEs with the knowledge, networks, and financial linkages needed to scale impact-driven innovations. Ultimately, Africa’s agricultural transformation depends on empowering its agribusinesses with the resources necessary to build resilient, climate-smart, and socially inclusive food systems. The CFSA Bootcamp demonstrated how strategic investment in SMEs can catalyse sustainable agricultural development, positioning these enterprises as key players in tackling food insecurity and climate challenges. Looking ahead, scaling similar programs will be vital in ensuring a more robust and equitable agrifood system across the continent.